Suinocultura e o potencial energético do biogás no município de São Miguel do Iguaçu - PR - Camilo, Nyara Chandoha (2017)
The West region of Paraná has an expressive production of swines and, consequently, of manure that comes from these animals. Swine biomass presents considerable potential for the production of biogas, which can be transformed into energy. This work had with objective to characterize and determine the energy potential of biogas from swine biomass in the city of São Miguel do Iguaçu - Paraná - Brazil. Twenty-five swine farms was selected by geo-referenced images, where a semi-structured questionnaire was applied through in loco visits. The properties were characterized with respect to the production system, size and management system, and the profile of the producer was determined, as well as their perception regarding the importance of swine and biogas. The average biogas production potential and the energy potential were calculated based on two methodologies, Hashimoto, Chen and Varel (1981) and IPCC (2006), and the values obtained were compared. Based on the results, the methodology of Hashimoto, Chen and Varel (1981) was selected for energy potential calculations. The data collected and the results of the calculations suggest that the region has an average biogas production potential of approximately 9,400 m³/day and an energy potential of 46,385 kWh/day. Such values can be considered relevant, so that it is invested in biodigestion systems and biogas energy generation in the locality. As a future perspective, in view of the values obtained, it is envisaged that studies for the implementation of condominial biogas production systems, linked to a microthermal power plant, could result in reduction of implementation costs and benefit for all those involved, as well as investment of private companies and/or government agencies could facilitate the access of swine farmers to this technology.